Contactless charge carrier mobility measurement in organic field-effect transistors - Roelofs, W. S. Christian; Li, Weiwei; Janssen, René A. J.; Leeuw, Dago M. de; Kemerink, Martijn (Organic electronics, 2014)
With the increasing performance of organic semiconductors, contact resistances become an almost fundamental problem, obstructing the accurate measurement of charge carrier mobilities. Here, a generally applicable method is presented to determine the true charge carrier mobility in an organic field-effect transistor (OFET). The method uses two additional finger-shaped gates that capacitively generate and probe an alternating current in the OFET channel. The time lag between drive and probe can directly be related to the mobility, as is shown experimentally and numerically. As the scheme does not require the injection or uptake of charges it is fundamentally insensitive to contact resistances. Particularly for ambipolar materials the true mobilities are found to be substantially larger than determined by conventional (direct current) schemes.